Noradrenergic inputs from the locus coeruleus to anterior piriform cortex and the olfactory bulb modulate olfactory outputs - Chi Geng; Ruochen Li; Shan Li; Penglai Liu; Yuxin Peng; Changyu Liu; Zhen Wang; Hongxing Zhang; Anan Li (Nature Communications)
Abstract Norepinephrine (NE) released from locus coeruleus (LC) noradrenergic (NAergic) neurons plays a pivotal role in the regulation of olfactory behaviors. However, the precise circuits and receptor mechanisms underlying this function are not well understood. Here, in DBH-Cre mice model, we show that LC NAergic neurons project directly to both anterior piriform cortex (aPC) and the olfactory bulb (OB). By using pharmacological and optogenetic manipulations in vitro and in vivo, we found that NE reduces the excitability of aPC pyramidal neurons directly via α2 receptors and that it bidirectionally regulates the activity of OB mitral cells via modulation of inhibitory inputs. Activation of the NAergic projection reduced both spontaneous and odor-evoked activity in the aPC/OB in awake mice, enhanced the odor-decoding ability of the aPC, and decreased the odor-decoding ability of the OB. Furthermore, activation of LC–aPC/OB NAergic projections accelerated odor discrimination and specific inactivation of the LC–aPC/OB NAergic pathway impaired olfactory detection and discrimination. These findings identify the mechanism underlying NAergic modulation of the aPC/OB and elucidate its role in odor processing and olfactory behaviors.